Impact of Anthropometric Characteristics on Football Performance by Playing Position - Chetan; Saxena, Vikas (Integrated Journal for Research in Arts and Humanities, 2024)
The purpose of the present study is to find out the correlation between anthropometric variables and different playing positions in football. The objective of this study is to examine and compare the different body measurements of district-level football players across different playing positions: defenders, midfielders, and forwards. Body measurements are critical anthropometric attributes that contribute significantly to a football player's performance, and understanding their variation across positions can provide valuable insights into position-specific training and talent identification. A sample of 90 players from Bhopal district-level teams was selected for the study, and their body measurements were assessed through standardized anthropometric kit. The findings suggest that position-specific anthropometric variable could enhance the performance of football players, and coaches should consider these differences when developing conditioning programs. The study highlights the importance of specific anthropometric characteristics in determining positional effectiveness on the football field. These findings suggest that coaches and scouts should incorporate anthropometric data into player recruitment and development strategies, allowing for position-specific training that enhances individual and team performance. Tailoring physical conditioning based on these characteristics could further optimize athletic output and overall gameplay.